Effect of between-set recovery durations on repeated sprint ability in young soccer players - Selmi, MA; Haj Sassi, R; Haj Yahmed, M; Moalla, W; Elloumi, M (Biology of Sport, 2016)
The purposes of this study were to examine the effect of between-set recovery duration on physiological responses (heart rate and blood lactate), rating of perceived exertion (RPE) and performance indices of repeated sprint sets (RSS) and to investigate their relationship with aerobic power. Twenty-four young male soccer players (age: 17.4 ± 0.32 years) performed three randomized RSS protocols consisting of 2 sets of 5x20 m with 15 s recovery between sprints and 1 min (RSS1), 2 min (RSS2) and 4 min (RSS4) between sets, and a multi-stage aerobic track test to estimate VO2max. Results showed that in contrast to RSS2 and RSS4, RSS1 leads to a large decline in performance expressed as the sum of sprint times (34.0±1.0 s, 34.0±1.1s and 34.6±1.1s, respectively) and a significant increase of both mean heart rate (124.0±9.7 bpm, 112.5±6.7 bpm and 137.3±12.4, respectively) and RPE (3.2±1.5, 3.4±1.2 and 6.3±1.4, respectively) with no change in blood lactate and peak HR between the three rest conditions. No significant correlations were obtained between estimated VO2max and any of the indices of the three RSS protocols. In conclusion, 1 min of recovery between sets is sufficient to ensure a significant decrease in performance in the second set, while 2 min and 4 min of recovery were long enough to provide maintenance of high intensity work in the second set. These findings would be useful for coaches and sport scientists when attempting to assess repeated sprint abilities, allowing coaches to accurately define the intended training goals in young soccer players.